Overvalued And Undervalued Stock? Comparative Case Study Using Discounted Cashflow Method - Yulia Sukma Hardyanti; Vita Via Puspita; Ika Atma Kurniawati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the intrinsic value of PT Indofood Sukses Makmur Tbk and PT Unilever Indonesia Tbk using the Discounted Cash Flow (DCF) method. The companies were selected based on their strategic role in the consumer goods sector and their attractiveness to investors. A descriptive quantitative approach was applied using secondary data from financial reports for 2022–2024. The results indicate that INDF shares are undervalued on 2022 until 2024, UNVR shares are overvalued on 2022 until 2023 dan undervalued on 2024. This discrepancy reflects differences in business structure and cash flow efficiency between the firms. The findings emphasize the importance of fundamental valuation in supporting rational and strategic investment decisions.